PENGARUH KEPEMIMPINAN DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PT. PANCARAYA KRISNA MANDIRI CABANG BANDUNG - Noorcikal Metasari; Yudiyanto Joko Purnomo (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2021)
This research was conducted on employees of PT. Pancaraya Krisnamandiri Bandung Branch. The purpose of this study was to determine how big the contribution of the influence of leadership and discipline to the performance of employees of PT. Pancaraya Krisnamandiri Bandung Branch. The research method used in this research is descriptive and associative methods. In this study, the unit of analysis is the individual, namely the performance of employees at PT. Pancaraya Krisnamandiri Bandung Branch. The sample in this study were 21 respondents. Sampling used in this research is saturated sampling technique. The analysis method uses path analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study showed that there was a partial or simultaneous influence on the leadership and discipline variables on employee performance. The implication of this research is that punishment and reward should be a point of concern, because the penalties are not yet firm and there is still a lack of reward for disciplined employees. Even though there is a clear SOP, in accordance with the statement that has a dominant answer, as well as the rewards given by employees for employees who work according to the SOP, there is no reward if employees practice discipline. So the company should try to provide rewards for disciplined employees in the future.